IS INDIA MOVING FROM RULE OF LAW TO RULE OF GUN AND JUDICIAL RESPONSIBILITY - Gupta, Gopal Krishan; Arti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rule of law will not be used in the execution of power. Article 21 of the law, which guarantees the right to life and personal liberty, contains a procedure for criminal investigations. It is essential, non-negotiable, and accessible to everybody. That right cannot even be infringed by the State. Nobody questions this. No one, not even the police or other investigating body, has the authority to penalize an accused person without following the proper legal procedures. Only the court has the authority to inflict a prison term or the death penalty after following all legal procedures and providing a fair trial and hearing. Until a person is proven guilty by the legal system, they are presumed innocent. The core of the Indian Constitution is found in Article 21. The framers of the Constitution placed the burden of protecting this right from infringement on the government, not even granting the state the power to violate it. An institution that has long been trusted to uphold and assist in enforcing the law is the police force. They have historically instilled confidence in the nation's residents by upholding security and providing the best possible protection for all. But recent events have shown that this was a myth, as it is difficult to fully trust the criminal justice system in light of the recent police interactions and violence that rocked the nation. After reviewing all available evidence and establishing the accused's guilt in a court of law, the burden of proof always rests with the prosecution. The nation's sluggish criminal justice system makes the police problem worse. Trials last for years on end, and the verdict is still up in the air, especially when it comes to the criminals who have financial, political, and physical clout. This is why there is pressure on the police to use shortcuts and illegal tactics. Conspiracy by the political elites and public backing are commonplace. The judiciary is given the authority to determine who is right or wrong. It punishes the wrongdoer without turning it into a retaliatory act and strives for true justice.